Resveratrol Stimulates Hydrogen Sulfide (H2S) Formation to Relax Murine Corpus Cavernosum. (6th October 2015) - Yetik‐Anacak, Gunay; Dereli, Mehmet V.; Sevin, Gulnur; Ozzayım, Ozge; Erac, Yasemin; Ahmed, Asif
Abstract: Introduction: Resveratrol (RVT) found in red wine protects against erectile dysfunction and relaxes penile tissue (corpus cavernosum) via a nitric oxide (NO) independent pathway. However, the mechanism remains to be elucidated. Hydrogen sulfide (H2 S) is a potent vasodilator and neuromodulator generated in corpus cavernosum. Aims: We investigated whether RVT caused the relaxation of mice corpus cavernosum (MCC) through H2 S. Methods: H2 S formation is measured by methylene blue assay and vascular reactivity experiments have been performed by DMT strip myograph in CD1 MCC strips. Main Outcome Measures: Endothelial NO synthase (eNOS) inhibitor Nω‐Nitro‐L‐arginine (L‐NNA, 0.1 mM) or H2 S inhibitor aminooxyacetic acid (AOAA, 2 mM) which inhibits both cystathionine‐β‐synthase (CBS) and cystathionine‐gamma‐lyase (CSE) enzyme or combination of AOAA with PAG (CSE inhibitor) has been used in the presence/absence of RVT (0.1 mM, 30 min) to elucidate the role of NO or H2 S pathways on the effects of RVT in MCC. Concentration‐dependent relaxations to RVT, L‐cysteine, sodium hydrogen sulfide (NaHS) and acetylcholine (ACh) were studied. Results: Exposure of murine corpus cavernosum to RVT increased both basal and L‐cysteine‐stimulated H2 S formation. Both of these effects were reversed by AOAA but not by L‐NNA. RVT caused concentration‐dependent relaxation of MCC and that RVT‐induced relaxation was significantly inhibited by AOAA or AOAA + PAG but not by L‐NNA. L‐cysteine caused concentration‐dependent relaxations, which are inhibited by AOAA or AOAA + PAG significantly. Incubation of MCC with RVT significantly increased L‐cysteine‐induced relaxation, and this effect was inhibited by AOAA + PAG. However, RVT did not alter the effect of exogenous H2 S (NaHS) or ACh‐induced relaxations. Conclusions: These results demonstrate that RVT‐induced relaxation is at least partly dependent on H2 S formation and acts independent of eNOS pathway. In phosphodiesterase 5 inhibitor (PDE‐5i) nonresponder population, combination therapy with RVT may reverse erectile dysfunction via stimulating endogenous H2 S formation.Yetik‐Anacak G, Dereli MV, Sevin G, Ozzayım O, Erac Y, and Ahmed A. Resveratrol stimulates hydrogen sulfide (H2 S) formation to relax murine corpus cavernosum. J Sex Med 2015;12:2004–2012.